Development of natural and innovative material for application as thermal insulation in buildings - Spinelli, Rodrigo; Lerin, Dantara; Spohr, Glauco L. S.; Pitol, Alana Francischett; Pasquali, Pedro Henrique Dall Agnol; Haetinger, Claus; Cambeiro, Faustino Patiño; Konrad, Odorico (Sustainability in Debate, 2020)
The advent of new technologies related to thermal insulation systems in civil construction helps buildings become more efficient, reducing their consumption of electric energy through air conditioning, and providing thermal comfort to users. The research aims to develop a facade cladding board for buildings, with thermal insulation starting from vacuum, and corn cob. Facade coatings with mortar finish were developed, filling them with developed materials. Three prototypes were executed in masonry of ceramic blocks, with dimensions of 60x60x64,0 cm. The Field Logger 512K (Lite) and PT100 sensors were used for data collection of external temperature and internal temperature of the prototypes. Solar radiation data were collected by the university weather station, model Davis-6450. It is worth noting the average internal temperature reduction in Prototype 2 and 3, compared to 1 (without isolation), which was 2.74 ° C and 8.05 ° C.